The Over-the-Hill-Gang - Yarbrough, Jean; Brennan, Walter, 1894-1974; Thomas-Spelling Productions; Cinetel Films ([Los Angeles, CA] : Thomas/Spelling Productions, 1969)
Classic comedic western, Captain Oren Hayes of the Texas Rangers takes a break to visit his daughter in a neighboring town. When he arrives he find's his daughter Hannah's husband Jeff is running for Mayor against a corrupt town boss, Nard Lundy. --
Originally broadcast on ABC.
Walter Brennan, Edgar Buchanan, Andy Divine, Jack Elam, Gypsy Rose Lee, Kris Nelson, Ricky Nelson, Pat O'Brien, Chill Wills, Edward Andrews.
Cinematographer, Henry Cronjager; editor, Joe Gluck; music, Hugo Friedhofer.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Texas Rangers -- Drama; Western films; Western television programs; Made-for-TV movies; Comedy films; Feature films; Internet videos; Streaming video